Complicaciones de diabetes mellitus tipo 2 atendidas en consulta externa del hospital teófilo dávila de enero a junio 2018 - Loaiza Beltran, Marian Andrea (Machala : Universidad Técnica de Machala, 2019)
Introduction: Diabetes mellitus (DM) is a chronic noncommunicable disease, according to the World Health Organization (WHO). There are acute complications (ketoacidosis and hyperosmolar coma), microvascular chronic (retinopathies and neuropathies) and macrovascular (coronary heart disease, cerebrovascular and peripheral vascular diseases). Objective:To analyze the complications of Type 2 Diabetes Mellitus, reviewing statistics of patients treated at Teófilo Dávila Hospital during January to June 2018, to strengthen the knowledge about this pathology. Development: It is a descriptive study of case reports. The collection of data from the Daily Registry of Outpatient Consultations and Care (RDACCA) in the statistics department of the Teófilo Dávila Provincial Hospital, data are obtained from January to June of the year 2018 Conclusion:The most common complication is diabetic neuropathy, while in Colombia the most common complication is diabetic nephropathy. According to the statistics of the Hospital Teófilo Dávila, the most frequent complications are: diabetic neuropathy, diabetic nephropathy and neurological.
Introducción: La diabetes mellitus (DM), es una enfermedad crónica no transmisible, de acuerdo por la Organización Mundial de la Salud (OMS). Existen complicaciones agudas (cetoacidosis y coma hiperosmolar), crónicas microvasculares (retinopatías y neuropatías) y macrovasculares (cardiopatía coronaria, enfermedades cerebrovasculares y vasculares periféricas). Objetivo:Analizar las complicaciones de Diabetes Mellitus tipo 2, revisando estadísticas de pacientes atendidos en el Hospital Teófilo Dávila durante Enero a Junio 2018, para fortalecer el conocimiento sobre esta patología. Desarrollo: Es un estudio descriptivo de reporte de casos. La recolección de datos de Registro Diario de Consultas y Atenciones Ambulatorias (RDACCA) en el departamento de estadísticas en el Hospital Provincial Teófilo Dávila se obtienen los datos desde Enero a Junio del año 2018 Conclusión: La complicación más frecuente es neuropatía diabética mientras que en Colombia la complicación más frecuente es nefropatía diabética. Según la estadística del Hospital Teófilo Dávila, las complicaciones más frecuentes son: neuropatía diabética, nefropatía diabética y neurológicas.
Keywords: DIABETES MELLITUS; ENFERMEDAD CRONICA NO TRANSMISIBLE; COMPLICACIONES